Effectiveness of Oxidation Ponds in Pig Farm Wastewater Treatment in Sarawak - Ling, T. Y.; Liew, C.F.; Modingin, A. (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Pig farm wastewater contains high concentrations of solids and nutrients. Operators are required to build oxidation ponds for the treatment of wastewater. However, there is a lack of information on the performance of the ponds being implemented in Sarawak. Therefore, in this study, wastewater quality from inflow and outflow of farms with 2-pond with and without separator. and 3-pond systems was investigated Comparing inflow and outflow concentrations. all the systems resulted in significant reduction of the parameters studied The order from the most efficient to the least was: 3-pond>2-pond>2-pond (separator). Most of the reduction of TSS, BODs and COD occurred in the first two ponds. The presence of the third pond resulted in large improvement in DO,AN, TN and TP. Comparing the final efJluent with the discharge standards proposed by Natural Resource and Environment Board (NREB) for TSS, BODs and COD, it was exceeded only by the 2-pond (separator) system.This indicates that even with so/id-liquiq separator. the size of the ponds and maintenance of the ponds are still essential to ensure good treatment and compliance to the proposed water quality standards.